Clinical manifestations and diagnosis of acute myeloid leukemia in a patient with a medical history of pulmonary tuberculosis (a case report) - O. M. Raznatovska (Zaporožskij Medicinskij Žurnal, 2020)
The aim is to familiarize practitioners with the initial clinical manifestations of acute myeloid leukemia and its diagnosis in a patient with a past medical history of pulmonary tuberculosis.